(untitled) (Research, Society and Development, 2022)
Sleep is essential for several important physiological and metabolic processes that will favor the maintenance of good health. The objective of the present study was to review the literature on the influence of sleep on the quality of the diet of nighttime health workers. A narrative literature review was carried out to synthesize and analyze the scientific studies on the proposed theme. Therefore, a search was carried out between August and October 2021 for original publications in the Google Scholar database between the years 2017 and 2021. After the initial search, 12 articles were obtained, of which five were selected. Of these selected articles, 100% were developed with nurses. Negative changes in sleep quality were found in four studies, and of these, one study found an association between increased body mass index and worsening sleep quality. Regarding the influence of sleep on diet quality, all studies found low dietary quality, changes in eating behavior, especially in relation to higher caloric intake, saturated fat and sweets intake, and lower water consumption by nurses who worked in the hospital. night time. The results of the present review demonstrate the prevalence of sleep disorders among nurses, mainly with negative impacts on the quality of food. In this sense, regular monitoring of sleep quality is suggested, as well as the incorporation of healthy habits, to promote health benefits for this population.